TATA KELOLA PENANGGULANGAN BENCANA ALAM Suatu Deskripsi Inter-Relasi dan Kesiapan Para Pihak dalam rangka Rehabilitasi-Rekonstruksi Rumah Warga Terdampak Pascagempa di Kabupaten Tanah Datar - Erwin - (Universitas Andalas, 2014)
At the time of the earthquake affecting substantial losses due to the damage they cause, usually very high expectations of the people to the government for rehabilitation and reconstruction (rehabilitation and reconstruction) of homes affected. Therefore readiness to undertake the rehabilitation of earthquake remains an important concern by the parties in the response to natural disasters, both government and society. This study is a qualitative study to describe the experience of the parties in order to direct the rehabilitation of houses affected by the earthquake of 2007 in Tanah Datar, West Sumatra province. The results of this study found the application of the principles of transparency, participation and accountability in the interrelation between the government and society in the process of preparation and implementation of the rehabilitation of earthquake-affected neighborhoods. Open governance practices have proven quite successful even minimize complaints and public protests or other social conflict that impacts are not uncommon in post-disaster management in the region. Experiences of good practice organizing the rehabilitation of houses affected by the earthquake in Tanah Datar this would even be used as a pilot, and learning resources of many parties in implementing the governance of disaster management in the various regions